Myopericytoma at the Craniocervical Junction: Clinicopathological Report and Review of a Rare Perivascular Neoplasm. Issue 2 (8th June 2018) - Yang, Jimmy C; Venteicher, Andrew S; Koch, Matthew J; Stapleton, Christopher J; Friedman, Gabriel N; Venteicher, Emma M; Shin, John H
Abstract: BACKGROUND AND IMPORTANCE: Myopericytoma is an emerging class of neoplasm originating from the perivascular myoid cellular environment, previously classified as a variant of hemangiopericytoma. Most reported myopericytomas are found in soft tissues of the extremities; however, infrequent cases are described involving the central nervous system. Intracranial myopericytoma remains rare. Here, we describe the first report of myopericytoma occurring at the cervicomedullary junction in close proximity to the vertebral artery, mimicking a vascular lesion. CLINICAL PRESENTATION: A 64-yr-old woman presented with radiating neck pain. Magnetic resonance imaging revealed a well-circumscribed enhancing lesion adjacent to the vertebral artery-accessory nerve complex. She underwent a far lateral craniotomy and cervical laminectomy to obtain proximal vertebral artery control and adequate exposure of the lesion, which appeared most consistent with neoplasm at surgery. Histopathology revealed a grade I myopericytoma. A gross total resection was achieved, and the patient has no evidence of recurrence 3 yr after surgery. CONCLUSION: Tumors of perivascular origin include hemangiopericytoma, glomus tumor, myofibroma, and myopericytoma and are uncommon lesions intracranially. Consideration of and distinction among these perivascular tumors is critically important, as they each have distinct clinical behaviors and management. Myopericytoma can mimic other neoplastic and cerebrovascular pathologies, but it most commonly has a benign course and can be surgically cured if a gross total resection can be achieved. Rarer myopericytoma variants that adopt a more malignant course have been described, and ongoing molecular studies may identify mutations or activated signaling pathways that can be targeted to offer chemotherapeutic options in the future.